Association of SNPs in Microtus arvalis and clade infections by TULV-CEN.S and TULV-EST.S - Labutin, Anton; Saxenhofer, Moritz; White, Thomas; Heckel, Gerald (Zenodo, 2021)
The natural host ranges of many viruses are restricted to very specific taxa. Little is known about the molecular barriers between species that lead to the establishment of this restriction or generally prevent virus emergence in new hosts. Here, we identify genomic polymorphisms in a natural rodent host associated with a strong genetic barrier to the transmission of the European Tula orthohantavirus (TULV). We analyzed the very abrupt spatial transition between two major phylogenetic clades in TULV across the comparatively much wider natural hybrid zone between evolutionary lineages of their reservoir host, the common vole ( Microtus arvalis ). A genomic scan of 79 225 Single Nucleotide Polymorphisms (SNPs) in 323 TULV infected host individuals detected 30 SNPs that were associated with specific TULV clades in two replicate sampling transects. Focusing the analysis on 199 voles with evidence of genomic admixture at the individual level (0.1 - 0.9) supported statistical significance for all 30 loci. Host genomic variation at these SNPs explained up to 37.6% of clade-specific TULV infections. Genes in the vicinity of associated SNPs are involved in functions related to immune response or membrane transport. This study demonstrates the relevance of natural hybrid zones as systems not only for studying processes of evolutionary divergence and speciation, but also for the detection of evolving genetic barriers for specialized parasites. Funding provided by: Schweizerischer Nationalfonds zur Förderung der Wissenschaftlichen Forschung Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100001711 Award Number: 31003A_149585 Funding provided by: Schweizerischer Nationalfonds zur Förderung der Wissenschaftlichen Forschung Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100001711 Award Number: 176209